Pengaruh Kualitas Produk Dan Consumer Trust Terhadap Loyalitas Pelanggan Di Fortunate Coffee Cemara Asri - Gerald, Jovian; Sutarno, Sutarno (LPPM Universitas Dinamika Bangsa, 2024)
Fortunate Coffee is a cafe that provides healthy food that does not contain meat, milk, eggs, preservatives, or MSG. Fortunate Coffee uses only the best imported coffee beans to create its world-renowned coffee flavor. The purpose of this study was to examine how trustworthy products and high-quality service at Fortunate Coffee Cemara Asri affect customer loyalty. The statistical method is based on association and this study used a random sampling strategy to select 79 customers who made purchases between January and June 2023. Data processing used SPSS, while the analysis used a series of regression tests. You can represent the results of multiple linear regression analysis as Y = 6.526 + 0.255X1 + 0.254X2. Therefore, we can anticipate an increase or decrease in consumer loyalty by 0.255 times for every one-unit change in product quality. The same is true for consumer trust: a 0.254-fold increase is anticipated for every 1-unit increase in consumer trust. Initial findings indicate that consumer trust and product quality are significant determinants of customer loyalty. Keywords : Consumer Trust, Product Quality, Customer Loyalty